Effect of indoor environmental exposure on seminal microbiota and its application in body fluid identification. (September 2020) - Yao, Ting; Han, Xiaolong; Guan, Tianshan; Wang, Zhi; Zhang, Siqi; Liu, Changhui; Liu, Chao; Chen, Ling
Highlights: The polymicrobial community of semen have diverse origins. Single microbial marker may not suitable for semen identification, and it might be more appropriate to analysis in combination with the whole microbial community. Affected by exposure, the relative abundance of Staphylococcus exhibited a significant increase. Comparing semen with vaginal secretions and saliva, three kinds of body fluids could be distinguished based on 16s rDNA sequencing data. Abstract: Semen is a common body fluid type in forensic sexual assault cases. It is of great significance to effectively identify semen for restoring the crime scene and determining the nature of the case. Nowadays, microbiome-based method shows as a promising tool for forensic body fluid identification. To explore the environmental impact on microbial community of semen and its traceability, 16S rDNA high-throughput sequencing was conducted to ten paired semen samples. Affected by exposure, the diversity of microbial community decreased generally as the genus Staphylococcus exhibited a relatively significant increase. However, the genus Staphylococcus, Corynebacterium, Corynebacterium_1 were observed in almost all 20 samples. Community barplot analysis and heatmap analysis showed composition of the predominant microbe in semen at the phyla and genus level maintained basically, so that it could distinguish from vaginal fluid and saliva regardless of environmental exposure. Based on these results, we believe the application of single microbial marker may limit in semen identification, but the method depending on microbial community might be useful for distinguishing semen even under indoor exposure.